Pelestarian Kesenian Daerah Ranau di Sanggar Duagha Desa Pagar Dewa Kabupaten Oku Selatan - Saputri, Ayu; Tahyudin, Didi; Husin, Azizah (Journal of Nonformal Education and Community Empowerment, 2020)
This research aims to determine how the art preservation of the Ranau area is done by the Art Gallery of Duagha, judging by the aspects of nurturing, creation, and staging of art. This type of research is descriptive by using a qualitative approach. The subject of this study amounted to five people, consisting of one workshop builder, one workshop trainer, and three members of the workshop, as well as the data collection techniques on the study were observation techniques, interviews, and documentation. The results of the research in the art gallery Duagha seen from the Four indicators: (1) The indicator of preserving the arts, art Gallery Duagha has been maintaining the art of Ranau area by means of maintaining its characteristic, dance motion, ornaments on clothing, and also a crossfire in music; (2) The indicator of creation, art gallery Duagha has been doing creations by creating new arts and creating new creations; (3) Art performance indicators, Duagha Art Gallery has done so, by participating art competitions and also art performances; (4) The indicator of art training implementation, Duagha Art workshop to conduct art training with the method of training of skills.